2010
DOI: 10.1097/ncc.0b013e3181cb40a8
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Peer Education for Breast Cancer Screening and Health Beliefs in Eastern Turkey

Abstract: Peers can reinforce learning through ongoing contact. Peer education can be used to improve early diagnosis of breast cancer and breast cancer awareness in asymptomatic women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
43
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 21 publications
14
43
1
Order By: Relevance
“…Because the experimental groups' scores for knowledge and intention of breast cancer screening were statistically different, we conclude that group education improves participants' knowledge of the importance of routine breast cancer screening and motivates them to seek out screening services from health care providers. Although these results are consistent with those of similar previous studies (Burgess et al, 2008;Kim and Menon, 2009;Ceber et al, 2010;Gözüm et al, 2010;Secginli and Nahcivan, 2011). Group education can increase the knowledge and intention of breast cancer screening.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Because the experimental groups' scores for knowledge and intention of breast cancer screening were statistically different, we conclude that group education improves participants' knowledge of the importance of routine breast cancer screening and motivates them to seek out screening services from health care providers. Although these results are consistent with those of similar previous studies (Burgess et al, 2008;Kim and Menon, 2009;Ceber et al, 2010;Gözüm et al, 2010;Secginli and Nahcivan, 2011). Group education can increase the knowledge and intention of breast cancer screening.…”
Section: Discussionsupporting
confidence: 92%
“…Mass media campaigns, internet resources, and health education have been used to promote public awareness of breast cancer and the importance of routine screening for many years in Taiwan, but the effectiveness of these measures has not been assessed. Many studies have shown that education has a positive impact on women's knowledge of breast cancer and increases their participation in prevention and screening (Burgess et al, 2008;Kim and Menon, 2009;Ceber et al, 2010;Gözüm et al, 2010;Secginli and Nahcivan, 2011). Han et al (2009) found that a 120-min classroom training program combined with follow-up counseling significantly increased mammography, clinical breast exam, and BSE rates.…”
Section: The Effects Of Education Program On Knowledge and Intention mentioning
confidence: 99%
“…First, Wong et al (2007) found that peer educator academic performance was enhanced. [22] Second, Gözüm et al (2010) recommended that peers can support learning through continuous contact. Peer education can be utilized to enhance early diagnosis of breast tumors and breast cancer attentiveness in asymptomatic females.…”
Section: Discussionmentioning
confidence: 99%
“…(12,13) It was described that regular BSE is a simple and effective method in early diagnosis of breast cancer, (14,15) although the Brazilian National Cancer Institute did not stimulate breast self-examination as an isolated strategy. (26) Mammography is the most efficient method for screening breast cancer, whose sensitivity ranges from 85-90% and its specificity is approximately 95%.…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing this type of tumor may manifest as palpable lesion, it is necessary to know and to apply methods that allow diagnosis early: self-breast examination, and clinical examination by a trained team. (12)(13)(14)(15) The DCIS of the breast involves a heterogeneous group of neoplastic proliferation, non-invasive, with risk of recurrence and malignant transformation. (16) According to Boff and…”
Section: Introductionmentioning
confidence: 99%